2006
DOI: 10.1097/00003081-200609000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Misoprostol Administration for Cervical Ripening and Labor Induction

Abstract: Intravaginal misoprostol has been shown to be an effective agent for cervical ripening and induction of labor. Vaginal application of misoprostol has been reported in over 9000 women worldwide and seems to have safety profile similar to that of endocervically and intravaginally administered dinoprostone. Concern arises with the use of higher doses of intravaginal misoprostol (50 mcg or more) and the association with uterine contractile abnormalities and for this reason, use of low-dose misoprostol regimen has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 64 publications
0
51
0
3
Order By: Relevance
“…But in that study misoprostol was used in the dose of 25µg every three hourly. Similarly a study by Wing et al, [7] and a systematic review by Crane et al, [4] have shown that misoprostol is more effective than dinoprostone. But since the dose schedules are different and involved higher doses, it is difficult to make direct comparisons.…”
Section: Methodsmentioning
confidence: 90%
“…But in that study misoprostol was used in the dose of 25µg every three hourly. Similarly a study by Wing et al, [7] and a systematic review by Crane et al, [4] have shown that misoprostol is more effective than dinoprostone. But since the dose schedules are different and involved higher doses, it is difficult to make direct comparisons.…”
Section: Methodsmentioning
confidence: 90%
“…However, excessive uterine contractility resulting in fetal distress is a cause for concern. [9][10][11][12][13][14] Comparing the oral and vaginal administrations of misoprostol, oral administration is easier and has greater acceptability among women. Further, absorption is more rapid and possibly more predictable, with a peak serum concentration following oral administration of 34 minutes and a half-life of 20-40 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Induction of labour with this analogue does not affect the frequency at which caesarean section is required. There is an increase in the rate of uterine hyperstimulation resulting in changes in fetal heart rate (FHR) pattern and staining of the amniotic fluid with meconium but without any apparent deleterious effect on the outcome [3][4][5][6][7][8][9][10] (for reviews [11][12][13] ).…”
Section: Introductionmentioning
confidence: 99%